The late effects of fetal growth patterns. Issue 4 (21st June 2006) - Bloomfield, F H; Oliver, M H; Harding, J E
Abstract : The immediate prenatal and postnatal consequences of reduced fetal growth have long been known. The longer term associations between reduced birth weight and adult disease risk are also now well established. Reduced fetal growth is usually detected late in gestation, and the assumption has been that this is the time when factors regulating fetal growth have their greatest effect. However, recent evidence suggests that both the growth trajectory of the fetus and its adaptive responses to the prenatal and postnatal environment may be determined in the period around the time of conception.